PERUBAHAN KOMPOSISI VEGETASI DAN STRUKTUR POHON PADA PLOT MEIJER (1959-2009) DI GUNUNG GEDE, JAWA BARAT - Zuhri, Musyarofah; Mutaqien, Zaenal (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
After Meijer had conducted ecological study on Mt. Gede Pangrango in 1959, the subsequent study did not monitor its d inamics. This study aimed to compare current vegetation composition and tree structure with past 50 years data based on Meijer publication. One hectare permanent plot reconstructed at submontane zone to identi fy vegetation changes during 50 years on August 2009. Vegetation analyses method was similar with 50 years ago include field tree identification, diameter at breast height (dbh), tree height, and first branch height. Result showed the species richness decreased from 233 to 166 species, diversity index (H) slightly changed from 3.39 to 3.29, and similarity index indicated the differentiation of both tree communities was 51%. Further r nore, from 63 tree species presented in 2009, 47 species was similar with 50 years ago and 16 species know n as new record. Moreover, 18 tree species recorded in 1959 had lost in 2009 i.e., Ehretia javanica, Heli( 7ia javanica, Mischocarpus frutescens, Saurauia bracteosa, Wedlandia glabrata, etc. The highest abundance oi I both studies was Villebrunea rubescens. The changes of vegetation composition and tree structure may have been caused by (1) wind disaster occurred on 1984; (2) human pressured from the nearest village; and (3 ) natural forest regeneration towards climax condition.